2008
DOI: 10.1111/j.1365-2133.2008.08671.x
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone inhibits murine hair growth via the androgen receptor

Abstract: Androgens inhibit hair growth in mice, and this inhibition might be caused by androgen-androgen receptor signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Studies using ARKO mice have in recent years provided several new insights into the androgen-AR system. Male ARKO mice demonstrate late-onset obesity , with decreased energy expenditure and enhanced insulin sensitivity (Fan et al 2005), disordered hypothalamic leptin signaling (Fan et al 2008), high turnover osteopenia , impaired brain masculinization (Sato et al 2004), dysregulation of the pituitary glucocorticoid feedback system (Miyamoto et al 2007), enhanced hair growth (Naito et al 2008), and altered skeletal muscle strength (Chambon et al 2010). ARKO mice are thus a useful tool for investigating androgen-AR activity in classical and nonclassical target organs and may have advantages over conventional models such as gonadectomized animals or administration of AR antagonists.…”
Section: Androgen Effects On Cardiac Remodelingmentioning
confidence: 99%
“…Studies using ARKO mice have in recent years provided several new insights into the androgen-AR system. Male ARKO mice demonstrate late-onset obesity , with decreased energy expenditure and enhanced insulin sensitivity (Fan et al 2005), disordered hypothalamic leptin signaling (Fan et al 2008), high turnover osteopenia , impaired brain masculinization (Sato et al 2004), dysregulation of the pituitary glucocorticoid feedback system (Miyamoto et al 2007), enhanced hair growth (Naito et al 2008), and altered skeletal muscle strength (Chambon et al 2010). ARKO mice are thus a useful tool for investigating androgen-AR activity in classical and nonclassical target organs and may have advantages over conventional models such as gonadectomized animals or administration of AR antagonists.…”
Section: Androgen Effects On Cardiac Remodelingmentioning
confidence: 99%
“…We also used both OCT and histological measurements to investigate the effect of helium-neon (He-Ne) laser (632.8 nm) irradiation on the hair follicle growth cycle in normal and testosterone-treated mice skin. In previous studies, it has been shown that exogenous androgens can be used to impair hair growth in albino mice [16] and pigmented mice [17,18] . The objective of this study was to investigate the role of low-level laser irradiation on the hair follicle growth cycle of normal as well as testosterone-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that DHT implantation remarkably suppressed hair regrowth after depilation. 22) As shown in Fig. 3, DHT-implanted mice treated with vehicle (Control-group) showed a remarkably retardation of hair regrowth.…”
Section: Hura Crepitans L Inhibits the Nt-4 Activation Induced By Dhmentioning
confidence: 99%
“…22) Male C57BL/6 mice (n=6) were purchased from Nihon SLC (Shizuoka, Japan) and maintained according to a protocol approved by the Animal Care and Use Committee of LION Corporation. The dorsal hair of male mice in the telogen stage (52 d postpartum) was removed with electric hair clippers and shavers, and the anagen stage was induced.…”
Section: Plasmid Construction and Luciferase Reporter Assaymentioning
confidence: 99%